Fast Pyrolysis of Biomass with a Concentrated Solar Power: a Review - Sri Aulia Novita; Santosa Santosa; Nofialdi Nofialdi; Andasuryani Andasuryani; Ahmad Fudholi; Perdana Putera (Green Engineering Society, 2022)
Indonesia's biomass energy potential is estimated at around 49,810 MW and is very adequate for the development go renewable energy. An example of a biomass conversion technique is pyrolysis which converts biomass into bio-oil. The optimum temperature for the pyrolysis process is 300-600 0C. Parameters that affect the pyrolysis process such as pretreatment of the material, moisture content and particle size of the material, the composition of biomass compounds, the effect of temperature, heating rate, gas flow rate, type of pyrolysis, and pyrolysis reactor. This is a thermochemical technique in which biomass waste is converted into solid fuel (char), producer gas (syngas), and liquid (bio-oil) without oxygen in a reactor. This article contains a comprehensive review of biomass conversion techniques to bio-oil using the solar energy-based fast pyrolysis method. Furthermore, the exposure used was based on the publication source, year, origin country, research methodology, and focus area. Most research has been empirical and mainly focused on fast pyrolysis and its influencing factors. There are several studies, information, and research recommendations described in this article.